To ‘enable our legal product to compete effectively with the transit market’: British American Tobacco’s strategies in Thailand following the 1990 GATT dispute - MacKenzie, Ross (Glob Public Health, 2015)
The opening of the Thai tobacco market, following action brought by the US Trade Representative under the GATT, is seen as a key case study of the tensions between trade and health policy. Interpretations of the dispute cast it, either as an example of how trade agreements undermine national policy making, or how governments can adopt effective public health protections compliant with international trade rules. As a UK-based company, British American Tobacco has been regarded as peripheral to this dispute. This paper argues that its close monitoring of the illegal trade during this period, the role of smuggling in the company’s global business strategy, and its management of the relative supply and pricing of legal and illegal products after market opening provide a fuller understanding of the interests and roles of transnational tobacco companies and the government in this dispute. The findings have important policy implications, notably the role of effective governance in countries facing pressure to open their tobacco sectors, need to better understand corporate-level activities within an increasingly globalized tobacco industry, and need to address the intertwined legal and illegal trade in implementing the WHO Framework Convention on Tobacco Control Protocol to Eliminate Illicit Trade in Tobacco Products.